Application of Proteomics for the Investigation of the Effect of Initial pH on Pathogenic Mechanisms of Fusarium proliferatum on Banana Fruit - Li, Taotao; Wu, Qixian; Wang, Yong; John, Afiya; Qu, Hongxia; Gong, Liang; Duan, Xuewu; Zhu, Hong; Yun, Ze; Jiang, Yueming (Frontiers in Microbiology, 2017)
Fusarium proliferatum is an important pathogen and causes a great economic loss to fruit industry. Environmental pH value plays a regulatory role in fungi pathogenicity, however, the mechanism needs further exploration. In this study, F. proliferatum was cultured under two initial pH conditions of 5 and 10. No obvious difference was observed in the growth rate of F. proliferatum between two pH values. F. proliferatum cultured under both pH conditions infected banana fruit successfully, and smaller lesion diameter was presented on banana fruit inoculated with pH 10-cultured fungi. Proteomic approach based on two-dimensional electrophoresis (2-DE) was used to investigate the changes in secretome of this fungus between pH 5 and 10. A total of 39 differential spots were identified using matrix-assisted laser desorption /ionization tandem time-of-flight mass spectrometry (MALDI-TOF/TOF-MS) and liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). Compared to pH 5 condition, proteins related to cell wall degrading enzymes and proteolysis were significantly down-regulated at pH 10, while proteins related to oxidation-reduction process and transport were significantly up-regulated under pH 10 condition. Our results suggested that the downregulation of cell wall degrading enzymes and other virulence proteins in the pH 10-cultured F. proliferatum severely decreased its pathogenicity, compared to pH 5-cultured fungi. However, the alkaline environment did not cause a complete loss of the pathogenic ability of F. proliferatum, probably due to the upregulation of the oxidation-reduction related proteins at pH 10, which may partially compensate its pathogenic ability.